INTRAUTERINE PROTEOLYTIC ENZYME THERAPY AMELIORATES CERVICAL MUCUS CHARACTERISTICS AND FERTILITY IN BUFFALOES SUFFERING CLINICAL ENDOMETRITIS - Dr. Neha Zaben Shaik; Jyothi, Kancharla; Anusha, Konjeti; Raghunath, Mullinti (The Indian Journal of Animal Reproduction, 2024)
A total of 30 pleuriparous buffaloes with signs of clinical endometritis were randomly divided into three groups of ten animals each. The buffaloes of Group I were administered intra uterinely with a single dose of proteolytic enzymes. Group II buffaloes were treated with ceftiofur sodium and Group III animals received no treatment. The cervical mucus was collected from the buffaloes of all groups before and after treatment during estrus for assessment of cervical mucus characteristics. After treatment, the consistency of cervical mucus was thin in 80, 60 and 20 per cent of buffaloes and mucus score of discharge was found to be clear in 90, 70 and 0 per cent in Group I, II and III buffaloes, respectively. The mean spinnbarkeit values of cervical mucus in Group I, II and III before the treatment were 7.24±0.79, 7.23±0.82 and 7.09±0.89 cm, and after the treatment were 15.79±0.64, 12.90±0.71 and 7.33±0.90 cm respectively. The mean pH values of Groups I, II and III before the treatment were 8.22±0.08, 8.12±0.10 and 8.13±0.07, respectively and after treatment, 7.10±0.03, 7.43±0.14 and 8.01±0.09, respectively. The difference in the mean spinnbarkeit values and pH were significant (p<0.05) in Group I and II in pre and post-treatment and between groups. Highest improvement in pH was observed in Group I animals treated with proteolytic enzymes followed by Group II and III. The first service conception rate was highest in Group I (44.44%) followed by Group II (42.85%) and Group III (0%). It can be concluded that intrauterine infusion of proteolytic enzymes may improve cervical mucus properties and fertility in buffaloes with clinical endometritis.